Narrative Coherence and Identity: Associations With Psychological Well-Being and Internalizing Symptoms - Vanden Poel, Louise; Hermans, Dirk (Frontiers in Psychology, 2019)
There are considerable differences in the way in which individuals remember and try to make meaning out of past personal experiences. One autobiographical memory characteristic that has been receiving growing attention is narrative coherence, or the extent to which an individual is able to construct coherent accounts of their autobiographical memories. Previously, differences in narrative coherence have been found to be related to well-being, with more coherent individuals displaying higher levels of well-being. This study aimed to extend previous findings by examining the associations between narrative coherence, identity functioning, psychological well-being, and internalizing symptoms in a sample of 395 American young adults (ages 18-30). We examined whether these associations differed within individuals as a function of the identity-relevance of the memory. In line with our prediction, narrative coherence was positively related to healthy identity functioning. However, the hypothesis that narrative coherence would be positively related to psychological well-being and negatively related to internalizing symptoms was only partially confirmed (i.e. only for personal growth and anxiety symptoms). These findings indicate that the relation between coherence and well-being might be more complex than originally assumed. Contrary to our predictions, it was not significantly more beneficial for an individual to narrate about a memory with high identity-relevance compared to a memory with low identity-relevance. Thus, it might be the individual’s general ability to include identity content within their narratives of personal experiences that moderates the association between coherence and well-being, rather than the identity-relevance of the specific memory. In the current study, we also found a significant gender effect, with women being more coherent than men. Furthermore, exploratory analyses indicated that being more coherent was associated with fewer internalizing symptoms and fewer identity-related struggles in men, but not in women. Possible explanations for the observed gender differences are discussed. Future longitudinal and experimental studies are needed to further clarify the link between narrative coherence, identity, and well-being.